2021
DOI: 10.1021/acs.energyfuels.1c02037
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Styrene Ionomers on the Dispersion of Asphaltenes in Crude Heavy Oil

Abstract: The purpose of this work was to investigate the effects of polystyrene-based acidic copolymers and ionomers on the dispersion of asphaltenes in heavy oil. In the first part of the work, we studied the effect of the addition of sulfonated polystyrene acidic copolymers (SSA) and Na-neutralized ionomers (SSNa) on asphaltene dispersion. It was found that the SSA copolymers and the low ion content SSNa ionomers did not show asphaltene dispersion enhancement. However, high ion content SSNa ionomers improved asphalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…30 The presence of the heteroatoms as well as the organometallic constituents (Ni, V, and Fe) is known to be responsible for association and aggregation of asphaltene molecules in crude oil. 66,68,69 The viscosity of heavy oil can be efficiently reduced through dissolution or dispersion of asphaltene, 10,23,30,37,68,74,93,94 which consequently improves oil recovery. 7,30,34,65,66 Although the concept has been researched using flowable heavy oils, 96 with the exception of very few ones on the extra-heavy oil (bitumen), 37 the ability of certain imidazolium ILs to disperse asphaltene and/or solubilize the highly viscous oils have been widely reported.…”
Section: Il−bitumen Interaction: Asphaltene Dispersionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 The presence of the heteroatoms as well as the organometallic constituents (Ni, V, and Fe) is known to be responsible for association and aggregation of asphaltene molecules in crude oil. 66,68,69 The viscosity of heavy oil can be efficiently reduced through dissolution or dispersion of asphaltene, 10,23,30,37,68,74,93,94 which consequently improves oil recovery. 7,30,34,65,66 Although the concept has been researched using flowable heavy oils, 96 with the exception of very few ones on the extra-heavy oil (bitumen), 37 the ability of certain imidazolium ILs to disperse asphaltene and/or solubilize the highly viscous oils have been widely reported.…”
Section: Il−bitumen Interaction: Asphaltene Dispersionmentioning
confidence: 99%
“…66,68,69 The viscosity of heavy oil can be efficiently reduced through dissolution or dispersion of asphaltene, 10,23,30,37,68,74,93,94 which consequently improves oil recovery. 7,30,34,65,66 Although the concept has been researched using flowable heavy oils, 96 with the exception of very few ones on the extra-heavy oil (bitumen), 37 the ability of certain imidazolium ILs to disperse asphaltene and/or solubilize the highly viscous oils have been widely reported. 30,37,72,93,94,10,23,30,37,74,93,94 Aside from the IL−clay interactions, electrostatic interactions may possibly occur between the ILs and oil components such as asphaltene, depending on the properties of the ILs.…”
Section: Il−bitumen Interaction: Asphaltene Dispersionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, for asphaltene with high polarity, the effect of existing polymers will be reduced, so the polar groups of polymers need to be modified to enhance the interactions with asphaltene accordingly. Polymers containing ions were also applied as asphaltene inhibitors . The styrene ionomers (SSNa) and styrene-methacrylic acid ionomers (SMANa) were synthesized as asphaltene dispersants.…”
Section: Introductionmentioning
confidence: 99%
“…Polymers containing ions were also applied as asphaltene inhibitors. 26 The styrene ionomers (SSNa) and styrene-methacrylic acid ionomers (SMANa) were synthesized as asphaltene dispersants. It is found that the SMANa ionomer is more effective than the SSNa ionomer.…”
Section: Introductionmentioning
confidence: 99%